Characterization of nickel lead sulphide thin films: X-Ray diffraction studies - Ho, Soon Min (Asian Research Publishing Network, 2017)
In this work, nickel lead sulphide thin films were grown by inexpensive and simple method, namely chemical bath deposition technique. Nickel sulphate, sodium thiosulfate and lead nitrate as the sources of Ni2+, S2- and Pb2+ ions, respectively. The effect of deposition period will be studied from 8 to 34 hours at room temperature. The obtained films were characterized by X-ray diffraction. The results reveal that the number of peaks was increased from two to five peaks as the deposition time increased up to 34 hours. In other words, more materials will be deposited onto substrates for longer deposition time.